The endoplasmic reticulum of trypanosomatids: An unrevealed road for chemotherapy - Sandes, Jana Messias; de Figueiredo, Regina Celia Bressan Queiroz (Frontiers in Cellular and Infection Microbiology, 2022)
The endoplasmic reticulum (ER) of higher eukaryotic cells forms an intricate membranous network that serves as the main processing facility for folding and assembling of secreted and membrane proteins. The ER is a highly dynamic organelle that interacts with other intracellular structures, as well as endosymbiotic pathogenic and non-pathogenic microorganisms. A strict ER quality control (ERQC) must work to ensure that proteins entering the ER are folded and processed correctly. Unfolded or misfolded proteins are usually identified, selected, and addressed to Endoplasmic Reticulum-Associated Degradation (ERAD) complex. Conversely, when there is a large demand for secreted proteins or ER imbalance, the accumulation of unfolded or misfolded proteins activates the Unfold Protein Response (UPR) to restore the ER homeostasis or, in the case of persistent ER stress, induces the cell death. Pathogenic trypanosomatids, such as Trypanosoma cruzi, Trypanosoma brucei and Leishmania spp are the etiological agents of important neglected diseases. These protozoans have a complex life cycle alternating between vertebrate and invertebrate hosts. The ER of trypanosomatids, like those found in higher eukaryotes, is also specialized for secretion, and depends on the ERAD and non-canonical UPR to deal with the ER stress. Here, we reviewed the basic aspects of ER biology, organization, and quality control in trypanosomatids. We also focused on the unusual way by which T. cruzi, T. brucei, and Leishmania spp. respond to ER stress, emphasizing how these parasites’ ER-unrevealed roads might be an attractive target for chemotherapy.